Peponocephala electra, mass stranding: A review - Perera García, José (2021)
Mass stranding events, which are stranding events involving two or more animals, have been reported for several odontocete species throughout history. The present work has listed mass stranding events for the species melon-headed whale (Peponocephala electra). A total of 40 of these mass stranding events, occurring between 1957 and 2021 worldwide, have been described. Results showed that the frequency of these events and the number of animals involved in each have increased in the last decades. Moreover, specific geographic locations, like Cape Verde and Japan, showed a higher incidence of these events. The highly social structure of melon-headed whales seems to play a role in their high frequency to mass strand and makes this species suitable as a representative to study and increase the knowledge on mass stranding events involving toothed whale species.